Reading of Jasser Auda's System Theory in the Law Verse on Women and Mosques - Shofaussamawati, S; Nikmah, Alfi; Azkiya, Muhammad Azka (Universitas Muhammadiyah Surakarta, 2025)
So far, there are still differences in interpretation and implementation in various places about women's worship in mosques. This study aims to explain and show the reading of Jasser Auda's system theory in legal verses related to women and mosques. The method used in this study uses the library research method by collecting information and data from Jasser Auda's books and website, previous research results, and various journal articles related to the problem being researched. As a result, the reading of system theory in legal verses about women and mosques through the six features offered, namely. The cognitive element in understanding legal verses related to women and mosques, in Auda's view there are dozens of verses in the Qur'an related to mosques whose content motivates Muslims, both men and women, to often go to mosques to get religious guidance, nur/divine light and knowledge. The element of wholeness (Al-Kulliyyah) Audah in determining the legal provisions about women and mosques is comprehensive, by exploring all verses related to mosques and followed by explanations from the Hadiths of the Prophet. Third, the element of openness (Opennes/al-Infitahiyyah. is carried out by Audah by displaying various opinions about the permissibility or prohibition of visiting the mosque with their respective arguments. Openness in the context of women and mosques also emphasizes that the relevant laws must take into account social and technological conditions.